Mensuração de desempenho nas organizações: a gestão de indicadores na biblioteca de Ciências Humanas da UFC - Gois, Maria Josineide (2009)
The aim of this study is to present the subject “organizational performance mensuration” through strategic management of indicators as instruments to control management information. It has as a purpose to develop and to apply performance mensuration taxonomy for the library. The research uses the functionalist approach and it is characterized for being descriptive and at the same time of practical aim. The guide basis for such investigation is the Sistema Nacional de Avaliação do Ensino Superior – SINAES, which institutes evaluation in higher education public institutions and the ISO standard 11620/2004 which spread knowledge on how performance measurement can be accomplished in the library. The Investigation was carried out at the Biblioteca de Ciências Humanas of the Universidade Federal do Ceará and aspects concerning the analysis of the product, the delivery systems as well as of the processes were approached. The instrument developed was showed to be efficient and of easy application, whereas the necessary information sources seem to be accessible and available in the routine of the library and resulted in consistent and precious information for managers. As a conclusion we can say that the performance systematic mensuration use is an efficient tool of control and accompaniment of management information, supporting the safe decision taking and the organizational planning, therefore, its dissemination must be encouraged.